The Emergence of Christian Elements in Chinese New Poetry: A Study of Church Schools - XUE Yuanyuan, (Journal of Research for Christianity in China (JRCC), 2025)
Church schools have nurtured a large number of outstanding poets for China's modern poetry scene, including Bing Xin, Chen Mengjia, Liang Zongdai, Lu Zhiwei, Xu Zhi, Liu Tingfang, Liu Tingwei, and Zhao Zichen. Their unique religious education infused Christian elements into these poets' works. The worship services, curriculum design, library resources, journal publications, and club exchanges at these schools provided modern poets with opportunities to engage with Christian culture. While such exposure did not necessarily lead to Christian identification among the poets, Christian influences—regardless of their personal impressions of Christianity—had already subtly imprinted themselves on their spiritual dispositions through the educational environment of church schools.
Keywords: Church schools Chinese modern poetry Christianity Christ-centeredness